PERAN DAN STRATEGI KOMUNITAS SAVE STREET CHILD SIDOARJO UNTUK MEMBANGUN NILAI KARAKTER GOTONG ROYONG PADA ANAK JALANAN - Hilda Rizma Maulidyah; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2022)
The purpose of this study is to find out the role and strategy of the Save Street Child Sidoarjo community to build the character value of mutual cooperation in street children. This research uses qualitative research methods with a descriptive approach. Data collection was carried out with participant observation, in-depth interviews, and documentation. The informants of this study were six people consisting of a community leader, three volunteers, and two street children of the Save Street Child Sidoarjo community. Determination of informants using purposive sampling. The research location of Lemah Putro Village, Sidoarjo Regency. The research conducted has a focus on the role and strategy of the Save Street Child Sidoarjo community to build the value of mutual aid character. The character value of mutual cooperation in this study is the value of help, the value of anti-discrimination and the value of anti-violence. The results of the research on the role and strategy of the Save Street Child Sidoarjo community to build the value of mutual cooperation character are shown through the role of educators and the role of facilitators. The role of educators from the Save Street Child Sidoarjo community is demonstrated through raising awareness and providing information to street children. Meanwhile, the role of facilitator from the Save Street Child Sidoarjo community is carried out by arranging verbally and personal communication to parents of street children. Meanwhile, the strategy carried out by the Save Street Child Sidoarjo community in building the value of mutual cooperation character is to use a persuasive approach. In this case it is done by means of directing, guiding and creating a community environment comfortably. Keywords: role, Save Street Child Sidoarjo community, mutual aid.